2013
DOI: 10.1021/ez400169b
|View full text |Cite
|
Sign up to set email alerts
|

Surface Condensation of CO2 onto Kaolinite

Abstract: The fundamental adsorption of CO 2 onto poorly crystalline kaolinite (KGa-2) under conditions relevant to geologic sequestration has been investigated using a quartz crystal microbalance (QCM) and density functional theory (DFT) methods. The QCM data indicated linear adsorption of CO 2 (0−0.3 mmol of CO 2 /g of KGa-2) onto the kaolinite surface up through the gaseous state (0.186 g/cm 3 ). However, in the supercritical region, the extent of CO 2 adsorption increases dramatically, reaching a peak (0.9−1.2 mmol … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
41
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 30 publications
(40 reference statements)
2
41
0
Order By: Relevance
“…Micro gravimetric measurements from the QCM followed a procedure recently described by Schaef et al, (2014). 7-30 µg of clay were deposited on the active area of one or both sides of the quartz crystal and dried at 50°C.…”
Section: Methodsmentioning
confidence: 99%
“…Micro gravimetric measurements from the QCM followed a procedure recently described by Schaef et al, (2014). 7-30 µg of clay were deposited on the active area of one or both sides of the quartz crystal and dried at 50°C.…”
Section: Methodsmentioning
confidence: 99%
“…Considering the mineralogy of the Berea samples and the results of the image analysis, it appears that kaolinite has been affected by the CO 2 . Indeed some recent experimental studies pointed out that CO 2 can be adsorbed onto kaolinite (Schaef et al, 2014) and that interactions between clay minerals and supercritical CO 2 can lead to detachment and partial removal of inter-granular clay from the rock matrix as a consequence of CO 2 diffusion within the clay layer structures and related changes in the interlayer electrical forces (Berrezueta et al, 2013). This, in turn is likely to affect the elastic properties of the rock due to the fact that kaolinite removal in particular microstructural locations may lower the overall stiffness of the rock.…”
Section: Rock-fluid Interactionsmentioning
confidence: 99%
“…Yet, the maximum CO 2 sorption capacity of kaolinite and of certain shales tended to decrease with decreasing moisture content [59]. Additionally, CO 2 adsorption onto kaolinite surface initially increases with increasing CO 2 density, reaching a peak near 0.4 g cm -3 , before declining rapidly due to competition between the surface kinetics and energetics of the CO 2 -mineral surface and CO 2 -CO 2 interactions; DFT (density functional theory) studies confirmed that CO 2 adsorption at kaolinite surface is favored over CO 2 clustering up to the density of 0.34 g cm -3 [60]. For black shales, Nuttall et al [61] found a positive correlation between CO 2 sorption capacity and organic carbon content, whereas no correlation with the clay mineral content was observed.…”
Section: Physical Sorption Of Co 2 In Shale Caprockmentioning
confidence: 91%